EFEKTIVITAS PENDEKATAN BEHAVIORISTIK DALAM MENINGKATKAN DISIPLIN BELAJAR PESERTA DIDIK KELAS X - Herwantoro; Rahmadani, Putri; Hartini; Beni Azwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the behavioristic approach in improving the learning discipline of tenth-grade students. Learning discipline is one of the important factors influencing students' academic success. However, various disciplinary problems are still commonly found, such as late assignment submission, lack of focus during learning activities, and low compliance with academic regulations. The behavioristic approach is considered relevant in addressing these issues because it emphasizes behavior formation through stimulus, response, reinforcement, and punishment. This study employed a literature review method with a qualitative descriptive approach. The data sources consisted of secondary data obtained from national and international scientific journals, books, undergraduate theses, master's theses, conference proceedings, and relevant scholarly articles. These sources were collected from academic databases such as Google Scholar, Garuda, ResearchGate, DOAJ, and university digital libraries. Data collection was conducted through documentation and literature study using the stages of identification, selection, classification, and analysis of relevant literature published within the last 5–10 years. Data analysis involved data reduction, data presentation, and conclusion drawing. The findings indicate that the behavioristic approach is effective in improving the learning discipline of tenth-grade students, as reflected in increased compliance with learning regulations, greater academic responsibility, reduced indiscipline behaviors, and the development of positive study habits. Positive reinforcement, behavioral habituation, an educational reward and punishment system, and teachers’ consistency in implementing rules were identified as important factors contributing to the success of this approach. Therefore, the behavioristic approach is worthy of being applied as a learning strategy and guidance and counseling service to sustainably enhance students' learning discipline.